Reliability Analysis of Two-Unit Cold Standby and Warm Standby Outdoor Electric Power Systems in Stable Weather - Entesar AL-Esayeh (AlQalam Journal of Medical and Applied Sciences, 2025)
In this paper presents the reliability analysis two mathematical models representing electric power systems operating in fluctuating outdoor weather (i.e., normal and stormy weather) and compared between two models. Model I deal the reliability analysis of a single-server two-unit cold standby; Model II deals the reliability analysis of a single-server two-unit warm standby. for two systems with two different modes [normal, total failure]. System failure occurs when both the units fail totally. The failure rate and failed repair rate of a unit are constants. Laplace transforms of the various state probabilities have been derived and then reliability is obtained by the inversion process. Moreover, an important parameter of reliability, i.e., MTTF (mean time to failure), the variance transition of time to failure of the system, system availability and steady-state availability are derived. The failure times of operating/spare units and repair time of failed units are exponential distributed. Certain important result has compared between two systems في هذه الورقة تقدم تحليل الموثوقية لنموذجين رياضيين يمثلان أنظمة الطاقة الكهربائية العاملة في طقس خارجي متقلب (أي الطقس العادي والعاصف) ومقارنة بين نموذجين. يتعامل النموذج الأول مع تحليل الموثوقية لوحدة احتياطية باردة ذات خادم واحد ووحدتين؛ ويتعامل النموذج الثاني مع تحليل الموثوقية لوحدة احتياطية دافئة ذات خادم واحد ووحدتين. لنظامين بنمطين مختلفين [طبيعي، فشل كلي]. يحدث فشل النظام عندما تفشل كلتا الوحدتين تمامًا. معدل الفشل ومعدل إصلاح الوحدة الفاشلة ثابتان. تم اشتقاق تحويلات لابلاس لاحتمالات الحالة المختلفة ومن ثم تم الحصول على الموثوقية من خلال عملية العكس. علاوة على ذلك، تم اشتقاق معلمة مهمة للموثوقية، أي متوسط الوقت حتى الفشل، وانتقال التباين لوقت فشل النظام، وتوافر النظام وتوافر الحالة المستقرة. يتم توزيع أوقات فشل الوحدات العاملة/الاحتياطية ووقت إصلاح الوحدات الفاشلة بشكل أسي. تمت مقارنة بعض النتائج المهمة بين نظامين